2015
DOI: 10.3146/0095-3679-42.2.138
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofBradyrhizobiaInoculant Formulation with Phorate in New Peanut Fields

Abstract: Peanut (Arachis hypogaea L.) is a legume and requires nodulation by Bradyrhizobia to convert atmospheric N into a plant usable form. Peanut inoculants place large volumes of viable Bradyrhizobia near the emerging root of the plant to infect it ensuring N-fixation. Peanut seedlings are susceptible to feeding by thrips (Thysanoptera: Thripidae), which transmit Tospovirus leading to tomato spotted wilt (TSW) and can result in yield decline. Phorate is a common in-furrow insecticide used to reduce thrips feeding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Certain pesticides and fertilizers applied with commercial inoculants can impact BNF (Jordan et al, 2010). For example, the fungicide pyraclostrobin adversely affected BNF while prothioconazole and the insecticides acephate, imidacloprid, and phorate did not affect BNF (Jordan et al, 2010(Jordan et al, , 2017Tubbs et al, 2015). Co-applying fungicide with crop protection and enhancement products could explain inadequate inoculant performance that requires correction with applied N.…”
mentioning
confidence: 99%
“…Certain pesticides and fertilizers applied with commercial inoculants can impact BNF (Jordan et al, 2010). For example, the fungicide pyraclostrobin adversely affected BNF while prothioconazole and the insecticides acephate, imidacloprid, and phorate did not affect BNF (Jordan et al, 2010(Jordan et al, , 2017Tubbs et al, 2015). Co-applying fungicide with crop protection and enhancement products could explain inadequate inoculant performance that requires correction with applied N.…”
mentioning
confidence: 99%
“…In contrast to tebuconazole, pyroclostrobin applied in the seed furrow reduced the efficacy of the inoculant and, subsequently, yield (Jordan et al, 2010). Tubbs et al (2015) reported that phorate applied in the seed furrow did not adversely affect nodulation or peanut response to Bradyrhizobium inoculant. In addition to concerns over inoculant performance, seed is the single most expensive input in peanut crops (Bullen and Jordan, 2015), and determining if agrochemicals adversely affect peanut stand establishment is important.…”
mentioning
confidence: 99%